The Effects of Recombinant Human Lactoferrin on Immune Activation and the Intestinal Microbiome Among Persons Living with Human Immunodeficiency Virus and Receiving Antiretroviral Therapy. (5th February 2019) - Sortino, Ornella; Hullsiek, Kathy Huppler; Richards, Elizabeth; Rupert, Adam; Schminke, Andrea; Tetekpor, Namo; Quinones, Mariam; Prosser, Rachel; Schacker, Tim; Sereti, Irini; Baker, Jason V
Abstract: Lactoferrin modulates mucosal immunity and targets mechanisms contributing to inflammation during human immunodeficiency virus disease. A randomized placebo-controlled crossover clinical trial of recombinant human (rh) lactoferrin was conducted among 54 human immunodeficiency virus–infected participants with viral suppression. Outcomes were tolerability, inflammatory, and immunologic measures, and the intestinal microbiome. The median age was 51 years, and the median CD4 + cell count was 651/µL. Adherence and adverse events did not differ between rh-lactoferrin and placebo. There was no significant effect on plasma interleukin-6 or D-dimer levels, nor on monocyte/T-cell activation, mucosal integrity, or intestinal microbiota diversity. Oral administration of rh-lactoferrin was safe but did not reduce inflammation and immune activation. Clinical Trials Registration : NCT01830595. Abstract : Recombinant human lactoferrin treatment in persons living with human immunodeficiency virus and receiving antiretroviral therapy did not significantly change inflammation within blood, nor the intestinal microbiota. Additional strategies are needed to reduce inflammation by targeting intestinal dysbiosis and mucosal immunity.